Synthesis, ferroelectric and optical properties of (Pb,Ca)TiO3 thin films by soft solution processing - Pontes, F. M.; Pontes, DSL; Leite, E. R.; Longo, Elson [UNESP]; Santos, EMS; Mergulhao, S.; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2003)
Calcium modified lead titanate sol was synthesized using a soft solution processing, the so-called polymeric precursor method. In soft chemistry method, soluble precursors such as lead acetate trihydrate, calcium carbonate and titanium isopropoxide, as starting materials, were mixed in aqueous solution. Pb0.7Ca0.3TiO3 thin films were deposited on platinum-coated silicon and quartz substrates by means of the spinning technique. The surface morphology and crystal structure, dielectric and optical properties of the thin films were investigated. The electrical measurements were conducted on metal-ferroelectric-metal (MFM) capacitors. The typical measured small signal dielectric constant and dissipation factor at a frequency of 100 kHz were 299 and 0.065, respectively, for a thin film with 230 nm thickness annealed at 600degreesC for 2 h. The remanent polarization (2P(r)) and coercive field (E-c) were 32 muC/cm(2) and 100 kV/cm, respectively. Transmission spectra were recorded and from them, refractive index, extinction coefficient, and band gap energy were calculated. Thin films exhibited good optical transmissivity, and had optical direct transitions. The present study confirms the validity of the DiDomenico model for the interband transition, with a single electronic oscillator at 6.858 eV. The optical dispersion behavior of PCT thin film was found to fit well the Sellmeir dispersion equation. The band gap energy of the thin film, annealed at 600degreesC, was 3.56 eV. The results confirmed that soft solution processing provides an inexpensive and environmentally friendly route for the preparation of PCT thin films.
Keywords: thin films; ferroelectric; synthesis chemical; Pb0.7Ca0.3TiO3